Impacts of Soil Freeze–Thaw Process and Snow Melting Over Tibetan Plateau on Asian Summer Monsoon System: A Review and Perspective - Wang, Chenghai; Yang, Kai; Zhang, Feimin (Frontiers in Earth Science, 2020)
Surface diabatic heating over the Tibetan Plateau (TP) is crucial for the onset and development of Asian summer monsoon (ASM), which is closely connected with the snow-melting and freeze-thaw (SM-FT) processes in spring. This study reviews the recent processes about studies on the effects of SM-FT on climate system over ASM region. This review has showed that, SM-FT in spring plays a dominant role in seasonal and inter-annual variations of surface diabatic heating over TP, which also have significant relationship with ASM activity. Moreover, anomalies of SM-FT over TP significantly affect summer precipitation in Eastern China (EC). FT-SM in spring over TP would be a robust factor in ASM system. The possible mechanism associated with the impacts of SM-FT on the summer general circulation in East Asia is also discussed. Under the climate change background, variations in regimes of frozen soil and snow have great potential effects on climate in East Asia and globe. However, great uncertainties in the estimation of diabatic heating over TP (especially over the western TP) during spring still confine our understanding about the effects of TP thermal forcing on ASM activity. It’s suggested that, improvement in the simulation of SM-FT process in models is an effective approach for reducing biases of climate projection in future.